Larvicidal activity of granulated pharmaceutical products using Indonesian holy basil leaf extract - Azis Ikhsanudin; Lolita Lolita; Zayyana Septya Ramadani (International Journal of Public Health Science (IJPHS), 2021)
Ocimum sanctum Linn, known as holy basil, is a larvicide, which is relatively safe compared to synthetic insecticides. This study investigates the larvicidal activity of a granule formulation of Indonesian holy basil leaf extract against third larval instar of Aedes aegypti. The extract of holy basil leaves was obtained by a maceration process with 96% ethanol. The granule was formulated with various concentrations of holy basil leaf extract, including F1 (2000 ppm), F2 (4000 ppm), and F3 (6000 ppm). The extract contained terpenoid, alkaloid, saponin, flavonoid, and polyphenol compounds. The extract granules had a moisture content of 3.01%, flowability of 1.51 seconds, and dispersion time of 1.09 seconds. The mortality rates of mosquitos treated with the different formulation groups were significantly different from positive control with values of 25.33% (F1), 50.67% (F2), and 90.67% (F3). In conclusion, the granulated formulation of holy basil leaf extract has a larvicidal LC50 of 4405.803 ppm and LC90 of 6080.714 ppm. Therefore, a granulated pharmaceutical product derived from holy basil leaf extract could be developed as a potent larvicide to control dengue fever.